PENGARUH KECERDASAN EMOSIONAL TERHADAP KETERAMPILAN RENANG GAYA DADA - Meri Haryani; Safri Irawan; Nurkhiroh Siregar; Arief Ibnu Haryanto; Juni Isnanto (STKIP Subang, 2024)
The high and low academic achievement in the breaststroke swimming lecture process depends on the swimming skills possessed. It is suspected that this is influenced by emotional intelligence. This study uses a quantitative research method with a correlation focus to test how emotional intelligence affects breaststroke swimming skills. The study population of female students of FIK-UNJA totaling 39 people. The total sampling technique for taking samples of the entire population was used as a sample of 39 people. Data were collected using a Likert-scale questionnaire to measure emotional intelligence data, skill observation sheets to measure breaststroke swimming skills. The results of the data analysis showed that the value of the emotional intelligence path coefficient X1 affecting swimming skills was within the normal range, statistically significant, and showed a linear relationship. Specifically, the results of the study showed that emotional intelligence contributed around 27.35% of the variation in swimming skills. Thus, it can be understood that emotional intelligence makes a major contribution to the influence of breaststroke swimming skills in female students. For this reason, in the lecture process, it is necessary to pay attention to and improve the level of emotional intelligence.